Model Pembelajaran Berpengaruh Dalam Berpikir Kritis Pada Peserta Didik - Hibatullah, Mahbubah Lihani; Masnawati, Eli; Ghozali, Solchan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
Learning model aims to build a learning atmosphere that supports and is in line with learning styles of students. Based on the results initial analysis conducted in class 5 MI Darul Ulum Tambakrejo Waru Sidoarjo, that teacher center learning using traditional learning methods. This situation causes students to not have critical thinking skills. The solution to dealing with this problem is through the application project-based learning model. The purpose writing is to provide analysis results related to the influence learning models on critical thinking skills in students. The type of research used is using quasi-experiments. The results calculation average percentage of students' pretests before using the PJBL model obtained score of 51.8% or were in "Low" category. While the results calculation average percentage of students' pretests after implementing the PJBL learning model obtained score 76.1% in the "High" category. The results calculation average percentage of students' pretests using the conventional model obtained score 51.6% or were in the "Low" category. Meanwhile, the results calculation average percentage of students' pretests on the use of conventional models obtained value 71.3% in the "High" category. The conclusion drawn is that increasing critical thinking skills can be improved by using learning models.